Fossil-Bearing Concretions of the Araripe Basin Accumulated During Oceanic Anoxic Event 1b - Bom, M. H.H.; Kochhann, K. G.D.; Heimhofer, U.; Mota, M. A.L.; Guerra, R. M.; Simões, M. G. [UNESP]; Krahl, G.; Meirelles, V.; Ceolin, D.; Fürsich, F.; Lima, F. H.O.; Fauth, G.; et al. (American Geophysical Union (AGU), 2023)
Fossils from the Araripe Basin (northeastern Brazil) are known for their remarkable preservation of vertebrates and invertebrates, even including soft tissues. They occur in carbonate concretions within organic carbon-rich strata assigned to the Romualdo Formation. Here we present integrated stable isotope, elemental and microfossil records from the Sítio Sobradinho outcrop, Araripe Basin, northeastern Brazil. Our results imply that black shales hosting fossil-bearing carbonate concretions within the lower Romualdo Formation were deposited during Oceanic Anoxic Event (OAE) 1b (Kilian sub-event). Our high-resolution multi-proxy approach allows identifying four phases of environmental evolution. After a pre-event phase, an early phase (onset of the negative carbon isotope excursion—nCIE) of water column stratification and reduced oxygenation likely preconditioned the system for organic carbon burial and preservation. A second phase (peak nCIE) was characterized by an intensified hydrological cycle and continental runoff, as well as increased influx of terrestrial organic matter. High input of continent-derived nutrients might have enhanced biological productivity in the epicontinental sea, ultimately leading to increased organic carbon fluxes and burial, as well as carbonate dissolution at the seafloor. All together, these paleoenvironmental conditions resulted in expansion of an oxygen minimum zone (OMZ), favoring taphonomic processes that led to the excellent preservation of diverse macro- and microfossils. The nCIE recovery phase was characterized by reduced nutrient supply and organic carbon burial. Organic carbon sequestration in such paleoenvironments likely contributed to the recovery (increase) of stable carbon isotope (δ13C) records in the deep ocean during the Kilian sub-event of OAE 1b.
Keywords: Aptian-Albian; carbonate concretions; Cretaceous; Kilian subevent; Romualdo formation